Testosterone in ancient hair from an extinct species. (13th August 2018) - Koren, Lee; Matas, Devorah; Pečnerová, Patrícia; Dalén, Love; Tikhonov, Alexei; Gilbert, M. Thomas P.; Wynne‐Edwards, Katherine E.; Geffen, Eli
Abstract: Testosterone is a key regulator in vertebrate development, physiology and behaviour. Whereas technology allows extraction of a wealth of genetic information from extant as well as extinct species, complementary information on steroid hormone levels may add a social, sexual and environmental context. Hair shafts have been previously used to sequence DNA from >50 000 14 C years old Siberian woolly mammoths ( Mammuthus primigenius ). Hair‐testing has also been used to measure endogenous steroids in multiple extant species. Here we use small quantities of woolly mammoth hair samples to measure testosterone, and a genomics‐based approach to determine sex, in permafrost‐preserved mammoths dated to c . 10 000–60 000 14 C years. Our validated method opens up exciting opportunities to measure multiple steroids in keratinized tissues from extinct populations of mammals. This may be specifically applied to investigating life histories, including the extinct Quaternary megafauna populations whose remains are preserved in the permafrost throughout the northern hemisphere.